2017
DOI: 10.1037/pspi0000100
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity through shared disadvantage: Highlighting shared experiences of discrimination improves relations between stigmatized groups.

Abstract: Intergroup relations research has largely focused on relations between members of dominant groups and members of disadvantaged groups. The small body of work examining intraminority intergroup relations, or relations between members of different disadvantaged groups, reveals that salient experiences of ingroup discrimination promote positive relations between groups that share a dimension of identity (e.g., 2 different racial minority groups) and negative relations between groups that do not share a dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
190
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(204 citation statements)
references
References 98 publications
(142 reference statements)
14
190
0
Order By: Relevance
“…Furthering our argument for the importance of group‐based empathy, empathic ties seem to be important in the formation and maintenance of groups, and also in responses to discrimination (e.g., Cortland et al ., ). Social identity theory (Tajfel & Turner, ) suggests that social groups are formed when individuals feel similar to one another on a particular dimension.…”
Section: Indirect Effects Of Hate Crime: An Intergroup Emotions Perspmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthering our argument for the importance of group‐based empathy, empathic ties seem to be important in the formation and maintenance of groups, and also in responses to discrimination (e.g., Cortland et al ., ). Social identity theory (Tajfel & Turner, ) suggests that social groups are formed when individuals feel similar to one another on a particular dimension.…”
Section: Indirect Effects Of Hate Crime: An Intergroup Emotions Perspmentioning
confidence: 97%
“…This similarity may help group members understand and feel what their fellow group members experience; that is, perceptions of similarity may help to foster strong empathic ties within groups. In addition, Cortland et al (2017) found that perceptions of similarity, this time across disadvantaged groups (Black people and gay people), increase empathyand also support for pro-action in the face of discrimination (Exp 2).…”
Section: Group-based Empathy: Neglected But Importantmentioning
confidence: 97%
See 2 more Smart Citations
“…Stigma solidarity often functions as an individual difference in which some individuals endorse this belief more strongly than others (Chaney et al., ), but it can also be situationally activated. For example, participants who are asked to first consider the similarities between two stigmatized groups, such as the parallels between the fight for interracial marriage and same‐sex marriage, are more likely to adopt a belief in stigma solidarity (Cortland et al., ).…”
Section: Stigmatized‐identity Cues Communicate Broadly To Social Groupsmentioning
confidence: 99%